Life cycle assessment of air transportation and the Swiss commercial air transport fleet. (January 2018) - Cox, Brian; Jemiolo, Wojciech; Mutel, Chris
Graphical abstract: Highlights: Life cycle assessment results for 72 common aircraft types and flight distances. Assesses the Swiss air transport sector from 1990 to 2050. Future aircraft expected to be 25–50% cleaner per passenger kilometer. Fleet impacts likely to increase, even under optimistic scenarios. Abstract: In this work we present a life cycle assessment of air transportation, the Swiss commercial aircraft fleet, and its potential development from 1990 to 2050. We first perform a life cycle assessment of air transport with 72 common aircraft types for different flight distances. These results are globally valid. Based on these results, a parameterized model of 5 aircraft size categories is developed that includes variation in aircraft production year, flight distance and maximum seating capacity. Future aircraft improvement is modelled with two scenarios that consider conservative and optimistic assumptions regarding future improvements to aircraft weight, fuel efficiency, aerodynamics, and exhaust emissions. In a third step, this model is calibrated to Swiss and European conditions and used to calculate the environmental burdens from Swiss passenger and freight civilian air transport. The model is found to accurately predict national aircraft fuel consumption to within 7% accuracy over a 25 year period, with the exception of the aftermath of the terrorist attacks of 2001. Results show that, despite significant improvements in per passenger kilometer emissions, overall environmental burdens due to air transportation are likely to continue increasing in the future due to rapidly increasing demand. Results further show that as exhaust emissions from aircraft are further reduced, the main cause of many environmental impacts caused by air transport will be due to upstream impacts of kerosene production, and not the direct operating of aircraft.